Challenges for the Applications of Human Pluripotent Stem Cell-Derived Liver Organoids - Chang, Mingyang; Bogacheva, Mariia S.; Lou, Yan-Ru (Frontiers in Cell and Developmental Biology, 2021)
The current organoid culture systems allow pluripotent and adult stem cells to self-organize to form three-dimensional (3D) structures that provide a faithful recapitulation of the architecture and function of in vivo organs. In particular, human pluripotent stem cell-derived liver organoids (PSC-LOs) can be used in regenerative medicine and preclinical applications, such as disease modeling and drug discovery. New bioengineering tools, such as microfluidics, biomaterial scaffolds, and 3D bioprinting, are combined with organoid technologies to increase the efficiency of hepatic differentiation and enhance the functional maturity of human PSC-LOs by precise control of cellular microenvironment. Long-term stabilization of hepatocellular functions of in vitro liver organoids requires the combination of hepatic endodermal, endothelial, and mesenchymal cells. To improve the biological function and scalability of human PSC-LOs, bioengineering methods have been used to identify diverse and zonal hepatocyte populations in liver organoids for capturing heterogeneous pathologies. Therefore, constructing engineered liver organoids generated from human PSCs will be an extremely versatile tool in in vitro disease models and regenerative medicine in future. In this review, we aim to discuss the recent advances in bioengineering technologies in liver organoid culture systems that provide a timely and necessary study to model disease pathology and support drug discovery in vitro and to generate cell therapy products for transplantation.